Respuesta :
in elimination method you add/subtract both equations to cancel out a variable so you can solve for 1 variable.
since there is +y in the first equation and +y in the second equation, you can subtract both equations from eachother to only be left with x values:
(2x+y=11) (subtract each term)
- (x+y=9)
you get x=2.
now sub in x=2 to any of the 2 equations to find what y is.
2(2)+y=11
y=7
so the answer is (2,7) which means the 2 lines intersect at the point (2,7)
since there is +y in the first equation and +y in the second equation, you can subtract both equations from eachother to only be left with x values:
(2x+y=11) (subtract each term)
- (x+y=9)
you get x=2.
now sub in x=2 to any of the 2 equations to find what y is.
2(2)+y=11
y=7
so the answer is (2,7) which means the 2 lines intersect at the point (2,7)
First Multiply the whole second equation(x+y=9) by negative 2
so now you'll have -2x-2y=-18
using the second equation, you'll then subtract the first and second equations
so the x's will cancel out and you'll have -y=-7 which simplifies to y=7
with already having y then use the easiest equation (x+y=9) and plug 7 into the equation
so it will look like x+7=9
Subtract 7 from both sides of the equal sign and x will equal 2
so now you'll have -2x-2y=-18
using the second equation, you'll then subtract the first and second equations
so the x's will cancel out and you'll have -y=-7 which simplifies to y=7
with already having y then use the easiest equation (x+y=9) and plug 7 into the equation
so it will look like x+7=9
Subtract 7 from both sides of the equal sign and x will equal 2